PROSTHODONTIC CARE FOR ENLISTMENT AGE MEN OF THE WESTERN REGION OF UKRAINE: MORBIDITY, ANATOMICAL AND TOPOGRAPHIC STRUCTURE, STATE OF PROVISION AND PROGNOSIS - Rachynskyi, S.V.; Schnaider, S.A.; Labunets, O.V.; Diieva, T.V.; Labunets, V.A.; Stupnytskyi, R.M. (World of Medicine and Biology, 2020)
Dental examinations involved 294 men of enlistment age (185 of urban and 109 of rural population) under the age of 20 years old. The prevalence and intensity of the development of prosthodontic morbidity has been determined. The anatomical and topographic description has been provided for the extracted teeth and teeth for prosthodontic rehabilitation and their ratio was provided. Extremely unsatisfactory state of prosthodontic care provision for enlistment age men of urban and rural population has been found, the satisfaction of which was only 6.2% and 3.3%, respectively, for single crowns, with almost no manufacturing of bridge dentures and implant-supported dentures. The negative prognosis for the development of prosthodontic morbidity and increase in the scope of prosthodontic care has been proved. Ways to reform the system of organization and planning of the medical care for conscripts in the Armed Forces of Ukraine have been proposed.
Keywords: dental morbidity; enlistment age; prosthodontic care; single crowns; bridge dentures